COMPARISON OF OVERCONSOLIDATED CLAY SETTLEMENTS CALCULATED BY ANALYTICAL 1D TERZAGHI CONSOLIDATION AND BIOT NUMERICAL ANALYSIS - Arifan Jaya Syahbana; Dwi Sarah (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2012)
ABSTRACT Consolidation is a phenomenon where air and water in the soil skeleton (i.e clay soil) are forced out due to loading. This condition can occur when clay soil is subjected to loading resulted from pressure in laboratory test, land fill or embankment, building and other structures in the field. Many studies have examined the consolidation of soil through numerical methods and One Dimensional Consolidation Theory of Terzaghi but rarely find a comparison between them. This study aims to find comparison of settlement due to consolidation based on the two methods. A simple simulation using different thicknesses of soil and different loading condition was carried out on saturated and homogenous overconsolidated soil. The settlement calculations were performed by analytical Terzaghi method and numerical analysis. The results obtained for the varied thickness of the soil samples show varied value of relative error which indicates that thickness is one of the factors contributing to the discrepancy of settlement between the methods. Variation of loading condition in each sample showed that the calculation results of two methods would be the quite similar if the loading is in the range of 40-52 kN/m2. Greater loading out of that range would cause the results of analytical analysis to be less than the numerical analysis.